Root Influences Rhizosphere Hydraulic Properties through Soil Organic Carbon and Microbial Activity - Batista, Aline Martineli [UNESP]; Pessoa, Thaís Nascimento; Putti, Fernando Ferrari [UNESP]; Andreote, Fernando Dini; Libardi, Paulo Leonel (MDPI, 2024)
Processes of water retention and movement and the hydraulic conductivity are altered in the rhizosphere. The aim of this study was to investigate the physical-hydric properties of soil aggregates in the rhizosphere of annual ryegrass (Lolium multiflorum) cropped in a Kandiudalfic Eutrudox, taking into account aspects related to soil aggregate stability. Soil aggregates from rhizosphere soil (RZS) and soil between plant rows (SBP) were used to determine soil water retention curves (SWRCs) and saturated hydraulic conductivity (Ksat). In addition, properties related to soil aggregate stability, such as water-dispersible clay, soil organic carbon (SOC), and microbial activity, were also assessed. The higher microbial activity observed in the RZS was facilitated by increased SOC and microbial activity, resulting in improved soil aggregation (less water-dispersible clay). For nearly all measured matric potentials, RZS had a higher water content than SBP. This was attributed to the stability of aggregates, increase in SOC content, and the root exudates, which improved soil water retention. The increase in total porosity in RZS was associated with improved soil aggregation, which prevents deterioration of the soil pore space and results in higher Ksat and hydraulic conductivity as a function of the effective relative saturation in RZS compared to SBP.